UKURAN KINERJA AUDITOR KASUS KAP BANDUNG YANG TERDAFTAR DI OJK (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
The purpose of this study was to find out empirical evidence of how much auditor performance measure in 6 public accounting firms in the Bandung area.The method used for this research is a quantitative method with descriptive approach and verification analysis, the sample used is senior auditor, supervisor and partner in 6 public accounting firms in bandung area as many as 21 respondents and the analysis tools used are Double Linear Regression, Determination Coefficient, Correlation Coefficient, and t-test. The results of this study show that Auditor Experience, Professionalism and Integrity have a significant effect on Auditor Performance in 6 Public Accounting Firms in Bandung Area. While a positive relationship between experience, professionalism, auditor integrity and auditor performance. Keywords: Auditor Experience, Professionalism, Integrity and Auditor Performance